A Parent-Implemented, Technology-Mediated Approach to Increasing Self-Management Homework Skills in Middle School Students with Autism. Issue 2 (3rd April 2018) - Hampshire, Patricia K.; Allred, Keith W.
ABSTRACT: Students with Autism Spectrum Disorder (ASD) in secondary school settings (i.e., grades 6-12) typically struggle with multiple academic challenges. Critics have noted that secondary schools traditionally have not been particularly effective in helping students with ASD develop self-determination (e.g., self-management) skills, which are considered pre-requisites to success in academics. Thus, there is a significant need for increased parent-professional collaboration in secondary schools. This study examined the effectiveness of coaching parents to implement a technology-mediated (e.g., iPad) approach to increasing the homework-related self-management skills for mathematics of five middle school students with ASD. Results indicate that these five students significantly increased their math homework self-management skills as a consequence of effectively using iPad applications when coached by their parents.